-6(4b+7)=-4(6b-7)

Simple and best practice solution for -6(4b+7)=-4(6b-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(4b+7)=-4(6b-7) equation:


Simplifying
-6(4b + 7) = -4(6b + -7)

Reorder the terms:
-6(7 + 4b) = -4(6b + -7)
(7 * -6 + 4b * -6) = -4(6b + -7)
(-42 + -24b) = -4(6b + -7)

Reorder the terms:
-42 + -24b = -4(-7 + 6b)
-42 + -24b = (-7 * -4 + 6b * -4)
-42 + -24b = (28 + -24b)

Add '24b' to each side of the equation.
-42 + -24b + 24b = 28 + -24b + 24b

Combine like terms: -24b + 24b = 0
-42 + 0 = 28 + -24b + 24b
-42 = 28 + -24b + 24b

Combine like terms: -24b + 24b = 0
-42 = 28 + 0
-42 = 28

Solving
-42 = 28

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 4(1x-6)+6=6x-8 | | 6x-1=9x-10 | | 7x+4=3x-52 | | 1r-10=10r+8 | | 4+6(k-8)=8k-38 | | 8-(-16)= | | x^3+5x^2+x^2-5x-12x-60=0 | | 5x(6-3)= | | 4w+5w=51 | | 10(8m+9)=10(6m-3) | | 8x+-8y=5 | | X-366=415 | | -5x+9=2x-4 | | x+3x+54+2x=180 | | 8p-8=8(-6p-8) | | 2x-6x+4=-12 | | 6x^2-8x-11=0 | | 4m^2-36m= | | x(3x+54)(2x)=180 | | 31=9t-13t+7 | | 19-13p=17p-8 | | (-3n+5)(-5.7)= | | 1.5+.3(h-6)=.8h+2 | | -[6x-(3x+5)]=-4-[4(2x-4)-3x] | | 37+3n=-2 | | (5y-4)(6y-7)= | | 5+2k=3k-3 | | (-8x^4+6x+3)+(2x^4-2x^2+7)= | | 10X^4-6X^3+8X^2=0 | | 22j+11=4j-7 | | q=1000+25p+q | | 6+1(8x+12)= |

Equations solver categories